Literatur Review: Consumer Protection in Transactions of Tartar Removal Products on E-Commerce: A Legal and Policy Review - Ida Ayu Dinda Laksmi; I Nyoman Bagiastra; Luh Nyoman Alit Aryani (GLOBAL HEALTH SCIENCE GROUP, 2025)
The rapid growth of e-commerce has significantly transformed consumer purchasing behavior, including in the health and personal care sectors. However, the online sale of tartar removal products raises serious concerns regarding consumer protection, product safety, and regulatory oversight. This study aims to examine the adequacy of the existing legal framework and policy mechanisms in protecting consumers who purchase tartar removal products through e-commerce platforms.Methods: This research employed a literature review design using a comprehensive strategy. Articles were sourced from international research journal databases accessed via the internet, specifically ScienceDirect, PubMed, and Google Scholar. All searches were conducted in March 2025, focusing on articles published between 2016 and 2024. The keywords used in this literature review were adapted from Medical Subject Heading (MeSH) terms, including